Desain Gambar Teknis IPA Kapasitas 20 Liter/Detik - Anggrika Riyanti; Mitra Edyatma; Marhadi Marhadi (Jurnal Daur Lingkungan, 2020)
Meeting the need for clean water is very necessary, especially in remote areas, or areas that are difficult to get water that is suitable for consumption. Clean water treatment, in order to meet the needs of customers where the installed capacity is often used in rural areas or small cities, namely WTP 20 L / sec. To plan a 20 L / sec IPA it is necessary to calculate first, which is usually prepared by the government through the Indonesian National Standard, its function after calculating so that an IPA 20 L / sec unit is obtained, and can determine the budget plan. This study aims to make a picture of the operating units of the IPA capacity of 20 L / sec with the calculation standard of SNI SNI 7507-concerning Complementary Building Specifications for Water Treatment Installation Units, and SNI 19-6774-2002 for planning procedures for water treatment installation package units. Includes calculation of intake, pre-sedimentation facilities, coagulation treatment processes, flocculation, sedimentation, and filtration, disinfectants and reservoirs, so that later they can be applied especially in rural areas or small cities in order to obtain clean water that is suitable for consumption.